2018
DOI: 10.30843/nzpp.2018.71.163
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity risks from stink bugs to New Zealand kiwifruit identified in Chinese language literature

Abstract: Brown marmorated stink bug (BMSB), native to Asia including China, is a major invasive horticultural and crop pest in North America and Europe, and now threatens the southern hemisphere. BMSB has not established in New Zealand although it is regularly intercepted at its borders. Relatively little is known about the impact of BMSB on kiwifruit, an important horticultural crop in New Zealand; at least in English language literature. Searches were conducted in the Chinese National Knowledge Infrastructure (CNKI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…YSSB could also become an ecological and economic danger to other parts of the world outside its’ area of origin if proper conditions and circumstances arise [ 45 ]. As far as New Zealand is concerned [ 13 , 46 ], and based on the mapping study with BMSB [ 47 ], there is no doubt that YSSB could establish in the country if it arrives and would potentially have significant economic impacts on a range of important horticultural crops, such as stone fruit, apples, and kiwifruit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…YSSB could also become an ecological and economic danger to other parts of the world outside its’ area of origin if proper conditions and circumstances arise [ 45 ]. As far as New Zealand is concerned [ 13 , 46 ], and based on the mapping study with BMSB [ 47 ], there is no doubt that YSSB could establish in the country if it arrives and would potentially have significant economic impacts on a range of important horticultural crops, such as stone fruit, apples, and kiwifruit.…”
Section: Discussionmentioning
confidence: 99%
“…Besides BMSB, YSSB is another important stink bug pest on kiwifruit [8,9,13,15]. Both adults and nymphs of YSSB feed on leaves, flowers, buds, vines, and fruit [15], causing leaf yellowing, flower-, bud-, and fruit-drop or fruit deformation, respectively [8,22].…”
Section: Kiwifruitmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the past many Chinese publications have not been easily accessible to international audiences because of the use of a non-Latin based language script and publication in local journals. Previous studies have demonstrated that Chinese databases containing Chinese language literature provided more quantitative (i.e., the number of publications on the subject in question) and qualitative (i.e., the quality of the information on that subject found therein) information than international English language databases for species in China which are of invasive concern to New Zealand [17,18]. A growing body of literature supports the need to access and interrogate non-English language data sources to obtain a more comprehensive collection of relevant publications and the information found within them at least in some disciplines [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%